2014
DOI: 10.1371/journal.pone.0091679
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Measurement of Dynamic Changes in Viral Load, Serum Enzymes, T Cell Subsets, and Cytokines in Patients with Severe Fever with Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infection caused by a novel Bunyavirus. Analysis on the dynamic changes of clinical, laboratory, and immunological abnormalities associated with SFTS in a concurrent study is lacking. Thirty-three SFTS patients were admitted to Jiangsu People's Hospital, Nanjing, China, and diagnosis was made based on the clinical symptoms and positive viral RNA detected by RT-PCR. Four patients deceased and twenty-nine survived. Blood samples were collected eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 16 publications
9
48
0
Order By: Relevance
“…Reports have shown that subpopulations of T cells were found to be changed at different phases of SFTSV-infected patients [16,19]. The present study revealed that CD4  CD25 Foxp3  cells were up-regulated in the circulating blood of patients with SFTS, and the percentage of CD4  CD25 Foxp3  cells negatively correlated with the leukocyte counts in patients with SFTS.…”
Section: Discussionsupporting
confidence: 57%
“…Reports have shown that subpopulations of T cells were found to be changed at different phases of SFTSV-infected patients [16,19]. The present study revealed that CD4  CD25 Foxp3  cells were up-regulated in the circulating blood of patients with SFTS, and the percentage of CD4  CD25 Foxp3  cells negatively correlated with the leukocyte counts in patients with SFTS.…”
Section: Discussionsupporting
confidence: 57%
“…Deceased patients had significantly higher viral loads than those of survivors when measured on days 7 -9 after the onset of fever, and viral loads gradually decreased during the recovery phase [9]. Since the microbiology laboratory of our hospital does not meet the facility criteria for dealing with the SFTS virus, we were unable to measure the viral load.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study showed that there was no significant difference in the lowest PLT count during the first week between 32 survival and deceased cases of SFTS in South Korea [10]. Li et al also reported that the PLT counts between both cases were very similar [9]. On the other hand, a study in northeast China showed that the lowest PLT count on admission or throughout hospitalization was associated with the severity of SFTS [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In convalescent stage, most of critical clinical parameters such as body temperature, hematologic values, and serum enzymes are normalized [1]. Immunologic analysis of SFTS patients revealed that elevation of CD 69+ T cells was evident in acute phase after onset of illness and that HLA-DR+ and CTLA4+ T cells were increased in the convalescent phase [17]. In addition, Deng et al[18] reported that concentrations of TNF-β, IL 6, IFN-γ, and IFN-γ-induced protein 10 were associated with disease severity.…”
mentioning
confidence: 99%